What building management system can offer to reduce power wastage both social and economical: brief discussion by taking Malaysian power infrastructure as a sample - Rasool, Zahid; Tariq, Waqar; Othman, Mohammad Lutfi; Jasni, Jasronita (The Standard International Journals, 2019)
As energy saving and zero energy building concept is flourishing, incorporation and installation of new systems are necessary to manage a building installed facilities. This particular paper reviews the literature concerning the energy savings achieved by installation of energy management systems and Implementation of energy management system and the reduction of the need for mechanical heating and cooling equipment permit the reduction of buildings' energy up to 50% and often entail no greater construction cost than conventional design. The paper also discusses the benefits and advantages of BMS or EBMS, the restrictions and hurdles of its implementation in Malaysian current power systems. Respective paper also highlighted the main reasons behind the respective challenges and respective solution, taking Malaysian society and current power generation and distribution /consumption system as a case sample also a bit review on some energy wasting factors like phantom load or standby energy wastage is included in this paper.